Writing my way through cancer - Schneider, Myra, 1936- (Jessica Kingsley Publishers, 2003)
Diagnosed with breast cancer in February 2000, poet and author Myra Schneider turned to her writing to help her come to terms with the experience. In this thoughtful and readable book, she illustrates how writing helped her through diagnosis, treatment and recovery as well as the change in self-image following her mastectomy. In her frank expression of intense fear, anger and doubt, Myra Schneider includes notes and finished poems written during her period of recovery. She also offers practical support in the form of therapeutic writing suggestions for cancer sufferers, whether they are experi.